IS AMINO ACID CHRONOLOGY APPLICABLE TO THE ESTIMATION OF THE GEOLOGICAL AGE OF SILICEOUS SEDIMENTS? - Harada N.; Kondo T.; Fukuma K.; Uchida M.; Nakamura T.; Iwai M.; Murayama M.; Sugawara T.; Kusakabe M. (My University, 2002)
There are few conventional dating methods that can be used to estimate the geological age of siliceous sediments on the order of 104-105 yr. In contrast, methods such as δ18O are available for dating carbonate-containing sediments in this geological age range. We focused on amino acid chronology as an alternative dating method for siliceous sediments. We analyzed the enantiomeric ratio (D-isomer/L-isomer) of aspartic acid (Asp) in bulk diatom assemblages in two siliceous sediment cores collected at Station (St.) 3 (approx. lat. 50°N, long. 165°E) and St. 5 (approx. lat. 40°N, long. 165°E) in the northwestern North Pacific. Radiocarbon and paleomagnetic ages were also obtained from both cores to use as reference ages. Two models, a reversible first-order kinetic model and a parabolic model, were used to determine the relationship between the D/L ratios of Asp and reference ages from the core at St. 5. By using these models, Asp ages were then estimated for the core at St. 3, and these ages were compared to paleomagnetic ages from that core. There was a large difference between Asp ages estimated by the first-order kinetic model and the reference ages. On the other hand, Asp ages estimated by the parabolic model were consistent with the reference ages. Therefore, an Asp dating method using the parabolic model is suitable for dating siliceous sediments. However, although generally the D/L ratio of Asp increased with increasing depth in the core at St. 5, the ratio did not continue to increase below about 10 m depth. The D/L ratio of Asp and the paleomagnetic age at that depth were 0.37 and 350 kyr BP, respectively. Therefore, the Asp racemization reaction apparently does not continue to progress in diatom frustules older than this age. This finding implies that Asp chronology can be used to determine ages up to about 350 kyr BP in sediments composed of diatom ooze. Although the Asp dating method using the parabolic model has a limitation of 350 kyr BP for siliceous sediments, it is available for the estimation of ages on the order of 104-105 yr BP, which is beyond the time range (up to 50 kyr BP) datable by the 14C method.
Keywords: AMINO ACIDS; CHRONOLOGY; SILICEOUS COMPOSITION; PACIFIC OCEAN